Dimethyl sulfide protects against oxidative stress and extends lifespan via a methionine sulfoxide reductase A‐dependent catalytic mechanism. Issue 2 (28th October 2016) - Guan, Xin‐Lei; Wu, Peng‐Fei; Wang, Sheng; Zhang, Juan‐Juan; Shen, Zu‐Cheng; Luo, Han; Chen, Hao; Long, Li‐Hong; Chen, Jian‐Guo; Wang, Fang
Summary: Methionine (Met) sulfoxide reductase A (MsrA) is a key endogenous antioxidative enzyme with longevity benefits in animals. Only very few approaches have been reported to enhance MsrA function. Recent reports have indicated that the antioxidant capability of MsrA may involve a Met oxidase activity that facilities the reaction of Met with reactive oxygen species (ROS). Herein, we used a homology modeling approach to search the substrates for the oxidase activity of MsrA. We found that dimethyl sulfide (DMS), a main metabolite that produced by marine algae, emerged as a good substrate for MsrA‐catalytic antioxidation. MsrA bounds to DMS and promoted its antioxidant capacity via facilitating the reaction of DMS with ROS through a sulfonium intermediate at residues Cys72, Tyr103, and Glu115, followed by the release of dimethyl sulfoxide (DMSO). DMS reduced the antimycin A‐induced ROS generation in cultured PC12 cells and alleviated oxidative stress. Supplement of DMS exhibited cytoprotection and extended longevity in both Caenorhabditis elegans and Drosophila . MsrA knockdown abolished the cytoprotective effect and the longevity benefits of DMS. Furthermore, we found that the level of physiologic DMS was at the low micromolar range in different tissues of mammals and its level decreased after aging. This study opened a new window to elucidate the biological role of DMS and other low‐molecular sulfides in the cytoprotection and aging.